Neural Correlates of Motor Imagery of Gait in Amyotrophic Lateral Sclerosis. Issue 1 (7th September 2020) - Abidi, Malek; de Marco, Giovanni; Grami, Fatma; Termoz, Nicolas; Couillandre, Annabelle; Querin, Giorgia; Bede, Peter; Pradat, Pierre‐Francois
Abstract : Background: Gait impairment is poorly characterized in amyotrophic lateral sclerosis (ALS), despite increasing evidence of extrapyramidal and cerebellar dysfunction. Gait impairment adds to the considerable motor disability of ALS patients and requires targeted multidisciplinary interventions. Purpose: To assess gait imagery‐specific networks and functional adaptation in ALS. Study Type: Prospective. Population: Seventeen ALS patients with lower motor neuron predominant (LMNp) disability, 14 patients with upper motor neurons predominant (UMNp) disease, and 14 healthy controls were included. Field Strength/Sequences: 3T / gradient echo echo planar (GE‐EPI). Assessment: Subjects performed a dual motor imagery task: normal and precision gait. The Movement Imagery Questionnaire – Revised Second Version (MIQ‐rs) was used to appraise movement imagery in each participant. Study group‐specific activation patterns were evaluated during motor imagery of gait. Additional generalized psychophysiological interaction analyses were carried out using the supplementary motor area, caudate, cerebellum, and superior parietal lobule as seed regions. Statistical Tests: Repeated‐measures analysis of variance (ANOVA) was used to compare time imagery and MIQ‐rs scores between groups. Size effects were also reported as partial eta squared (η2). One‐way ANOVA was performed to explore differences in terms of connexions during motor imagery tasks. Results: A significant increase in imagery time in UMNp patients compared to controls ( P  < 0.05) and LMNp ( P  < 0.05) during imagined gait was demonstrated. UMNp patients exhibited altered supplementary motor area, precentral gyrus, superior parietal lobule, and dorsolateral prefrontal cortex activation and increased orbitofrontal (pFDR(False Discovery Rate)  < 0.05), posterior parietal (pFDR < 0.05) caudate (pFDR < 0.05), and cerebellar (pFDR < 0.05) signal during imagined locomotion. Increased effective connectivity of the striato‐cerebellar and parieto‐cerebellar circuits was also demonstrated. Additional activation was detected in the insula and cingulate cortex. Data Conclusion: Enhanced striato‐ and parieto‐cerebellar networks in UMNp ALS patients are likely to represent a compensatory response to impaired postural control. Level of Evidence: 2 Technical Efficacy Stage: 5